2016
DOI: 10.1186/s12885-016-2973-y
|View full text |Cite
|
Sign up to set email alerts
|

Agonists and knockdown of estrogen receptor β differentially affect invasion of triple-negative breast cancer cells in vitro

Abstract: Background: Estrogen receptor β (ERβ) is expressed in the majority of invasive breast cancer cases, irrespective of their subtype, including triple-negative breast cancer (TNBC). Thus, ERβ might be a potential target for therapy of this challenging cancer type. In this in vitro study, we examined the role of ERβ in invasion of two triple-negative breast cancer cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 61 publications
4
50
0
1
Order By: Relevance
“…Since there is no ERα expressed in triple-negative breast cancer (TNBC), it is not yet known what the target of ERβ is, nor is it known whether ERβ is a driver of cancer in TNBC. In vitro studies with TNBC cell lines have shown that ERβ prevents invasiveness but does not affect proliferation (38)(39)(40). Studies with TNBC cell lines showed that ERβ can affect invasiveness by secretion of cystatins (41) and can increase innate immunity (42).…”
Section: Discussionmentioning
confidence: 99%
“…Since there is no ERα expressed in triple-negative breast cancer (TNBC), it is not yet known what the target of ERβ is, nor is it known whether ERβ is a driver of cancer in TNBC. In vitro studies with TNBC cell lines have shown that ERβ prevents invasiveness but does not affect proliferation (38)(39)(40). Studies with TNBC cell lines showed that ERβ can affect invasiveness by secretion of cystatins (41) and can increase innate immunity (42).…”
Section: Discussionmentioning
confidence: 99%
“…ERB-041 is a potent, selective ERβ agonist and has been tested in phase 2 clinical trial for treatment of rheumatoid arthritis [ 16 ]. ERB-041 has been found to suppress UVB-induced skin cancer in a mouse model [ 17 ] and inhibit invasion of triple-negative breast cancer cells in vitro [ 18 ]. A recent finding revealed inhibition of ovarian cancer cell proliferation by ERB-041 [ 19 ], but overall studies of ERB-041 on ovarian cancer were very limited.…”
Section: Introductionmentioning
confidence: 99%
“…The classical ERs are most evaluated in breast cancer, where their presence plays a significant role in choosing the best treatment regimen . Several functional data on ERα and ERβ have been obtained, and in triple‐negative breast cancer cell lines ERβ activation by agonists inhibited the invasiveness of the cancer cells in vitro . In prostate cancer, ERα promotes metastasis, while ERβ has an antiproliferative effect .…”
Section: Discussionmentioning
confidence: 99%
“…38 Several functional data on ERa and ERb have been obtained, and in triple-negative breast cancer cell lines ERb activation by agonists inhibited the invasiveness of the cancer cells in vitro. 39 In prostate cancer, ERa promotes metastasis, while ERb has an antiproliferative effect. 30,40 In ovarian cancer, ERb positivity was associated with poor overall survival (OS) and patients with cytoplasmic ERb2 splice variant positivity showed chemoresistance and worse disease outcome.…”
Section: Discussionmentioning
confidence: 99%